Genetics, molecular and cell biology of apoptotic cell death - Fajka-Boja Roberta (Acta biologica Szegediensis, 2015)
Apoptotic cell death is an integral part of development and cell turnover in multicellular organisms. Since early 1970’s, when apoptosis was defined on morphological basis, plethora of genes has been identified participating in initiation, execution and regulation of cell death. This article reviews these latest advances and describes our present understanding of the sequential events of apoptotic cell death, from the early steps of death receptor initiated and mitochondrial pathways to activation of caspases, and finally, the proper corpse clearance. It also discusses dysregulation of apoptosis, leading to various pathologies, such as cancer, autoimmune disease and neurodegenerative disorders.